Strategi Unggahan Konten Dakwah Salafi di Instagram Surau Televisi Official - Saipul Azhar; Fatimah Azzahra (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The use of strategies for uploading da’wah content on Instagram media is the main factor in the success of da’wah content developing on social media today. By using strategies for uploading da’wah content, it is hoped that content creators will be able to attract people to be more interested in listening to da’wah messages through the media. Instagram. This qualitative study aims to develop a strategy for uploading Salafi da’wah content via Instagram, which was carried aut by implementing the first 4 strategies: 1) Strategy for uploading informative salafi da’wah content, 2) Strategy for identification of salafi Da’wah Content in Production, 3) Strategy for Determining Upload times for Salafi Da’wah Content, 4) Strategy for Understanding the upload frequency Algorithm for salafi Da’wah Content. Televisio Surau is positioned as a research object. The data strategy for uploading Salafi preaching content via Instagram was collected through observation, interviews and data analysis reletad to this study. The results of this research inform that the upload strategy.